Perbedaan Hasil Pemeriksaan Kadar Glukosa Darah 2 Jam PP Dengan Menggunakan Glukometer Dan Analyzer Pada Penderita Diabetes Melitus - Ellies Tunjung Sari Maulidiyanti (Universitas Muhammadiyah Surabaya, 2017)
ABSTRACT Examination of blood glucose levels 2 hours pp is required to diagnose diabetes mellitus. Currently many clinical laboratories, hospitals and clinics are still modest usually use tool for the examination of blood glucose levels is by glucometer that emit relatively fast results. In contrast to the large hospital and clinical laboratories that have been developed have used the analyzer tool as an advanced tool that can check more parameters clinical examination which will get accurate results. To the authors want to prove whether there are differences in the results of blood glucose levels 2 hours pp using glucometer and analyzer. This research is experimental. The population in this study were patients with diabetes mellitus in hospital Throughout Siti Khadija. The samples used were serum and whole blood from the blood vena.Variabel free is the way 2-hour blood glucose tests using a glucometer and analyzer pp and the dependent variable is the blood glucose levels 2 hours pp. While the operational definition, examination of blood glucose 2 hours pp by using 2 kinds of tools, namely glucometer and analyzer. Methods of data collection of 20 samples taken from patients with DM in Hospital Khodijah Throughout Siti. To know the results used paired t test. The results showed that there were significant differences between the glucometer and glucose analyzer examination 2 hours pp based on the results of paired t test with sig value greater than 0.05 and the average levels of the glucometer 207.65 mg / dl and analyzer 193.85 mg / dl. Key word: glucose, glucometer, analyzer